PELAKSANAAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KESISWAAN DI MTs MISBAHUL HASAN ANDUNGSARI TIRIS PROBOLINGGO - Mohamad Ahyar Ma'arif (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
The Indonesian nation is facing a multidimensional crisis. From the results of studies of various disciplines and approaches, there seems to be a common view that all kinds of crises originate from moral or moral crises. This crisis is directly or indirectly, related to school or education issues. Research focus: (1) How to plan character education through student activities at Misbahul Hasan Andungsari Tiris Probolinggo MTs, (2) How to implement character education through student activities at Misbahul Hasan Andungsari Tiris Probolinggo MTs, and (3) How to evaluate character education through student activities at Misbahul Hasan Andungsari MTs Tiris Probolinggo. This research uses a qualitative approach with data collection methods of observation, interviews, and documentation. The data obtained were analyzed using descriptive analysis with steps of data reduction, data presentation and verification. The validity of the data uses triangulation of methods and sources. The results of the study show: (1) Planning for the implementation of character education through student activities in the Madrasah Tsanawiyah Misbahul Hasan Andungsari Tiris Probolinggo is relatively in accordance with planning in management. At least three elements of planning have been fulfilled namely: Choosing a set of activities, Deciding what to do next, when, how and by whom. When the implementation has been determined, the people directly involved are also clear, so the planning is only to run. (2) The implementation of character education through student activities in the Madrasah Tsanawiyah Misbahul Hasan Andungsari Tiris Probolinggo has been carried out according to applicable regulations, the madrasa head who has a model leadership in a hierarchy of needs has been able to move all components of the madrasa to consciously and responsibly jointly carry out their duties for the overall success of education., 3) Evaluation of character education through student activities in Tsanawiyah Madrasah Misbahul Hasan Andungsari Tiris Probolinggo has been relatively well underway. Evaluation developed by Madrasah Tsanawiyah Misbahul Hasan Andungsari Tiris. Keywords: Implementation of Character Education, Student Activities.